Vì x\in (0;1) nên ta đặt x=cost với t\in (0;\frac{\pi }{2}).Phương trình đã cho trở thành: 32cost(cos^2t-1)(2cos^2t-1)^2=1-\frac{1}{cost}.\Leftrightarrow 8sin^22t.cos^22t=1-cost\Leftrightarrow cost=1-2sin^24t.\Leftrightarrow cost=cos8t\Leftrightarrow t=\frac{2\pi}{9}; t=\frac{2\pi}{7};t=\frac{4\pi}{9}.Vậy phương trình đã cho có 3 nghiệm: x=cos\frac{2\pi}{7};x=cos\frac{2\pi}{9};x=cos\frac{4\pi}{9}.
Vì x\in (0;1) nên ta đặt $x=\cos t với t\in (0;\frac{\pi }{2}).Phương trình đã cho trở thành: 32\cos t(\cos^2t-1)(2\cos^2t-1)^2=1-\frac{1}{\cos t}.$$\Leftrightarrow 8\sin^22t.\cos^22t=1-\cos t\Leftrightarrow \cos t=1-2\sin^24t.$$\Leftrightarrow \cos t=\cos 8t\Leftrightarrow t=\frac{2\pi}{9}; t=\frac{2\pi}{7};t=\frac{4\pi}{9}.Vậy phương trình đã cho có 3 nghiệm: x=\cos\frac{2\pi}{7};x=\cos\frac{2\pi}{9};x=\cos\frac{4\pi}{9}.$